Mechanistic insights and biomarker discovery in immune cell aging and age-associated diseases - Upadhyay, Prabhat; Suhail, Aamir; Khanal, Pukar; Kumar, Sudhir (Frontiers in Immunology, 2025)
Immunosenescence is the progressive deterioration of immune function with aging and is driven by dynamic molecular and cellular interactions, most notably the chronic low-grade inflammation (inflammaging). This inflammatory state arises from lifelong antigen exposure, environmental stress, and hormonal shifts, culminating in paradoxical immune dysfunction: innate immune cells exhibit numerical expansion but functional decline, including impaired macrophage phagocytosis and diminished dendritic cell-mediated T cell priming. Advances in single-cell RNA sequencing have uncovered biomarkers of immune aging, such as upregulation of cyclin-dependent kinase inhibitors (CDKN1A/p21 and CDKN2A/p16INK4a) and senescence-associated secretory phenotype (SASP) components like IL-6, IL-8, and TNF-α. Concurrent epigenetic dysregulation, such as EZH2-dependent H3K27me3 alterations and global DNA methylation shifts, further orchestrates immune decline. The adaptive immune system undergoes profound remodeling, marked by thymic involution, skewed T cell receptor diversity, and B cell repertoire contraction, which collectively impair responses to novel antigens and vaccination efficacy. Elucidating these mechanisms provides a roadmap for targeting strategies to restore immune resilience in aging populations.